Using Webtoon Application to Develop Students’ Achievement in Reading - Rosdiana; Saiful; Ariana (Journal of Computer Interaction in Education, 2019)
This research aimed to find out the improvement of students’ reading achievement by using webtoon application to develop students’ achievement in literal comprehension. The subject of this research was 20 students at the eight grade students of SMP Negeri 3 Bontomarannu. The method that used was quantitative research with pre-experimetal research that consist of pre-test,treatment, and post-test. The researcher was used essay test and pair words as an research instrumental. The research findings indicated that using webtoon application was significant to improve the students’ achievement in literal reading in terms of main idea with the mean of pre-test was 60,75 and of post-test was 71,25, supporting details with mean of pre-test was 44,75 and of post-test was 51,25, and meaning words with mean of pre-test was 42,50 and post-test was 64,50. It was proved by students with the t-test value is is 6.488 >1.72913. It indicated that the result of t-test value in all of variable and indicator was higher than t-table value. It means there are improvement of students’ achievement in literal reading comprehension after being thaught through webtoon application.Therefore,it can be concluded that statistically hypothesis of H1 was accepted and the statistically hypothesis of HO was rejected.